Applied computer sciences in engineering. 5th Workshop on Engineering Applications, WEA 2018, Medellín, Colombia, October 17-19, 2018, Proceedings /: 5th Workshop on Engineering Applications, WEA 2018, Medellín, Colombia, October 17-19, 2018, Proceedings. Part I : (2018) - Unknown
No abstract available